Implementation of Collaborative Learning to Increase Motivation to Learn Aqidah Akhlak Class IX MTs Al-Hikmah Johar Karawang - Silvi Andriani; Aqmal Agustiansyah; Nadiya Meila Farhah; Dini Juliyanti; Camelyati Kulsum Padilah; Khalid Ramdhani (Noor: Journal of Islamic Studies, 2025)
This study aims to describe the effect of using the collaborative learning model on students’ learning motivation in the subject of Aqidah Akhlak in grade 9 at MTs Al-Hikmah Johar Karawang. The collaborative learning model emphasizes cooperation among students in solving problems, sharing knowledge, and helping each other to achieve learning goals. This approach is believed to enhance students’ motivation, active participation, and overall learning outcomes. This study uses a quantitative method with a simple random sampling technique, and data collection through pretests and posttests. The findings indicate that the implementation of collaborative learning had a positive and significant impact on improving students’ motivation in the Aqidah Akhlak subject. Based on these results, it can be concluded that the collaborative learning model is suitable for use in Islamic Religious Education to support the increase of both student motivation and learning achievement.